"Organised irresponsibility"? The Siemens corruption scandal of the 1990s and 2000s. Issue 3 (3rd April 2018) - Berghoff, Hartmut
Abstract: Siemens is one of the world's leading electrical engineering corporations. In 2006, a massive corruption scandal erupted, concluded in 2008 with a record fine. For Siemens the largest risk was being barred from government contracts. As a consequence, it replaced virtually its entire managing board, an unprecedented procedure in the history of the company. This article looks at the background of the scandal. Why did Siemens employees engage in corruption and dubious payments on such a grand scale? What does this case tell us about the compliance revolution that took place in the 2000s?